Character Education Management With Whole School Development Approach - M Aldi Irfan; Fadly Usman (Journal of Social Science and Economics, 2023)
The success of developing character education is not only the responsibility of the school (principals and teachers), but also the responsibility of parents. Because the development of character education is a shared responsibility between school principals, teachers and parents, each must be able to play a role as a supporter of the successful implementation of character education. This study aims to find out what forms of activity have been carried out in the implementation of character education management at MTs Sunan Bonang and describe character education management with a comprehensive school development approach at MTs Sunan Bonang Bangeran Mojokerto. The type of research used in this study is a type of qualitative research. Data collection was carried out at MTs Sunan Bonang Bangeran Dawarblandong Mojokerto in November 2021 - April 2022. A total of 6 people consisting of the Principal, Administrative Staff, Teachers, Parents, Students became respondents in this study. Data collection techniques in this study are observation, interviews, and document studies, while for the analysis of the data used is in accordance with the theory of Miles Huberman and saldana, the validity of the data used is Triangulation Sources and methods.The results showed that the implementation of Character Education Management at MTs Sunan Bonang Bangeran Dawarblandong in general has been carried out quite well, although not optimally. There are still some things that need to be perfected both in aspects of planning, organization, implementation and control and evaluation, as well as aspects of parental involvement in the character education management process. Activities or programs that have been implemented are as follows; (a) Giving an example and doing Habituation. (b) Designing and Planning. (c) Develop a character syllabus. (d) Develop character RPP. (e) Conducive Classroom management and friendly environment (f) Publish Communication Books. (g) Parents meeting (evaluation forum). (h) Student Program.